Non-cemented artificial kerogen plunger sample as well as preparation method and application thereof
By adding distilled water to kerogen powder to prepare cementless artificial kerogen plunger samples, the problem of chemical cementing agent interfering with the sample characteristics is solved, and more accurate experimental data and higher experimental efficiency are achieved.
Patent Information
- Application Number
- CN202411858047.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, when preparing artificial kerogen plunger samples, chemical cementing agents are often used, which interferes with the intrinsic characteristics of the sample, affects the accuracy of experimental results, and is prone to elastic rebound effect during the pressing process, affecting the integrity of the sample.
Using the preparation method without cement, the sample is mixed and shaped by adding distilled water to the kerogen powder, pressed into a plunger sample and dried to remove moisture, ensuring that the sample consists of kerogen powder only.
The intrinsic characteristics of kerogen are retained to the maximum extent, avoiding the interference of chemical cementitious agents on the nature of the sample, significantly improving the experimental efficiency and suppression success rate, and providing more accurate and representative experimental data.
Smart Images

Figure CN119738233A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of petrophysical analysis of oil and gas exploration, and in particular to an uncemented artificial kerogen plug sample and a preparation method and application thereof. Background Art
[0002] The uniqueness of natural shale lies in that it contains both inorganic minerals and organic components. The complexity of its multiple components makes it difficult to study the effect of organic matter on the elastic anisotropy of shale alone. This is of great significance for the evaluation of the "sweet spots" of unconventional reservoirs, the understanding of pore pressure and stress fields, the study of reservoir mechanical stability, and seismic exploration interpretation. Kerogen particles are mainly micrometer-sized. Commonly used microscopic analysis methods include nanoindentation and atomic force microscopy. Although these methods can characterize Young's modulus, they are limited in describing small strain elastic characteristics (such as velocity, bulk modulus, shear modulus, etc.) under wave field disturbance. Therefore, by pressing the extracted kerogen powder into a plug sample, the effects of these parameters can be separated and studied separately. Artificial kerogen plug samples can overcome the measurement limitations caused by organic matter dispersion, inorganic mineral and porosity interference, and strain differences in natural shales, isolate the influence of multiple variables, and simplify the complexity of research.
[0003] At present, the main methods for preparing artificial kerogen plug samples include cementation, cold pressing and hot pressing. However, existing research is often limited by the chemical binders used in traditional preparation methods. These binders will interfere with the intrinsic properties of kerogen during sample preparation, resulting in inaccurate or unrepresentative experimental results, making it difficult to provide accurate experimental samples for in-depth research on the elasticity, mechanical properties and electrical properties of organic matter in shale. In addition, binders such as epoxy resin may change the pore structure and permeability of kerogen, thereby affecting the adsorption properties of the sample. More importantly, kerogen itself has a certain viscoelasticity, which is prone to produce elastic rebound effect (springback) during the pressing process, causing elastic expansion and deformation of the sample, thereby affecting the success rate of pressing. These problems have seriously restricted the research on the physical properties of kerogen and other organic matter, and hindered technological innovation and development in related fields.
[0004] Therefore, how to quickly prepare kerogen plug samples without cementing agent has become one of the key challenges in rock physics elastic wave velocity testing, rock mechanics and rock electrical experiments. Solving this problem will provide a reliable basis for studying the physical properties of kerogen, support the fine geophysical characterization of unconventional reservoirs, promote the in-depth development of energy exploration such as shale gas and shale oil, and provide more accurate and representative experimental data for the geophysics and energy industries. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and to provide a non-cemented artificial kerogen plug sample and its preparation method and application. The prepared kerogen plug sample can be used for rock physics elastic wave velocity, electrical characteristics testing and rock mechanics experiments, so as to systematically reveal the rock physics and mechanical response mechanism of organic matter and kerogen in shale.
[0006] The conceived process of this application is as follows: the present invention does not rely on traditional binders such as epoxy resins, but rather adds distilled water to the kerogen powder for mixing and shaping. After the kerogen plunger sample is successfully pressed, it is dried to remove moisture and ensure that the sample consists only of kerogen powder. The prepared non-cemented artificial kerogen plunger sample is suitable for testing physical properties such as elastic wave velocity, mechanics and electrical properties of rock organic matter.
[0007] The purpose of the present invention can be achieved by the following technical solutions:
[0008] In one aspect, the present invention provides a method for preparing an uncemented artificial kerogen plug, comprising the following steps:
[0009] S1. Preparation of kerogen powder: First, crush the fresh rock sample into powder, then perform pretreatment, acid treatment, pyrite treatment, heavy liquid flotation and freeze drying on the powder sample, and wash the soluble organic matter with chloroform to obtain kerogen powder;
[0010] S2, batching and stirring: adding distilled water to the kerogen powder prepared in S1 and stirring thoroughly to make the kerogen powder have a certain viscosity;
[0011] S3, mold filling and pressing: the mixture of kerogen powder and distilled water stirred evenly in S2 is slowly added to the pressing mold in batches. Each batch of added powder needs to be compacted with a pressure column to ensure uniform force on the kerogen mixture during the subsequent pressurization process. Then the pressing mold is placed under a hydraulic press and pressurized to the final pressure.
[0012] S4. Depressurization and demoulding: After the final pressure of the kerogen powder is maintained for a period of time, the pressure is unloaded, and then the sample is demoulded. The pressed kerogen plunger sample is placed in an oven for drying to obtain a non-cemented artificial kerogen plunger sample.
[0013] Furthermore, in S1, the particle size of the powder sample is 75 to 180 μm,
[0014] Furthermore, in S1, the pretreatment includes soaking the powder sample in distilled water for 2 to 4 hours to remove upper liquid and impurities.
[0015] Further, in S1, the specific process of the acid treatment is:
[0016] Removing carbonate from the sample comprises adding hydrochloric acid to the pre-treated sample, heating to 60-70° C., stirring for 1-2 hours, removing the hydrochloric acid, washing with water and removing the washing liquid, wherein the volume of the hydrochloric acid required for each gram of the pre-treated sample is 6-8 mL, and the concentration of the hydrochloric acid is 6 mol / L;
[0017] Removing silicates from the sample comprises adding a mixed acid solution of hydrochloric acid and hydrofluoric acid to the sample after removing carbonates, heating to 60-70° C., stirring for 2 hours, removing the mixed acid solution, washing with water and removing the washing liquid, wherein the mixed acid solution is composed of hydrochloric acid and hydrofluoric acid in a volume ratio of 1-1:2, the concentration of the hydrochloric acid is 6 mol / L, the mass fraction of the hydrofluoric acid is 40%, and the volume of the mixed acid solution required for each gram of the sample after removing carbonates is 6 mL;
[0018] The steps of removing carbonate from the sample and removing silicate from the sample are repeated alternately until the sample no longer dissolves and its weight decreases.
[0019] Furthermore, in S1, the specific process of the pyrite treatment is: using 6 mol / L hydrochloric acid and arsenic-free zinc particles to remove pyrite.
[0020] Furthermore, in S1, the specific process of heavy liquid flotation and freeze drying is: using a relative density of 2.0 to 2.1 g / cm 3 The samples were subjected to layered flotation with heavy liquid to extract organic matter from the samples and remove residual inorganic minerals. The samples were then freeze-dried at a freezing temperature of -5°C and a drying temperature of 60°C.
[0021] Furthermore, in S1, the specific process of washing the soluble organic matter with chloroform is: using the Soxhlet extraction method, using chloroform as the extraction solvent, completely extracting the soluble organic matter, and further purifying the solid organic matter.
[0022] Furthermore, in S2, the mass ratio of the kerogen powder to distilled water is 10:1, and the stirring time is 0.25 to 0.5 h.
[0023] Furthermore, in S3, the specific process of pressurization is: firstly maintaining the pressure at the intermediate pressure for 0.5 h, and then directly increasing the pressure to the final pressure and maintaining the pressure for 6 h, and the final pressure is 20-30 MPa.
[0024] Furthermore, in S4, the specific process of the pressure unloading is: the pressure is reduced every 5 MPa, and the pressure holding time required for each pressure reduction is 0.5 to 6 hours, and the lower the pressure is, the longer the pressure holding time is. When the final pressure is reduced to 0 MPa, the pressure holding time is 6 to 8 hours.
[0025] Preferably, the drying temperature is 50-60°C and the drying time is 3-4 days. The properties of the kerogen sample will not be destroyed at the above temperature, until the difference in mass between the last two drying measurements is less than 0.01g, ensuring that the distilled water in the sample disappears completely.
[0026] On the other hand, the present invention also provides an application of an uncemented artificial kerogen plug sample, which can be used for physical testing of rocks, including density, porosity, microscopic and microstructural characterization, and elastic wave velocity measurement experiments.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) The present invention has important innovative significance in the technical field of geophysical models. Previously, the preparation methods of artificial shale mainly include cementation technology, cold pressing technology and hot pressing technology, all of which rely on chemical binders for solidification. However, the present invention provides a brand-new preparation scheme that breaks through the limitations of traditional methods. Unlike traditional processes, the present invention does not use any chemical binders in the pressing process of kerogen plug samples, but instead adds distilled water to the kerogen powder for mixing and shaping. After the kerogen plug samples are successfully pressed, they are further dried to remove moisture to ensure that the final sample consists only of kerogen powder. This innovative process retains the intrinsic properties of kerogen to the maximum extent, avoids the interference of chemical binders on the properties of the samples, and provides new ideas and technical breakthroughs for subsequent research on the measurement of elastic, mechanical and electrical properties of organic matter in shale, thus promoting technological innovation in this field.
[0029] (2) The present invention adopts the core technical concept of multi-stage and phased, provides a fast and simple method for preparing kerogen plug samples, optimizes the compression experiment process, effectively solves the problem of elastic rebound effect in the compression process of kerogen powder, and significantly improves the experimental efficiency. Compared with the traditional single-stage and single-stage compression method, the latter is prone to cause the kerogen plug sample to expand and deform, generate cracks, and then cause the sample to break or become irregular in shape, which is difficult to meet the requirements of rock physics experiments. The method adopted by the present invention can effectively shorten the pressurization time, avoid the change of pressure on the mechanical properties of kerogen powder, and prevent the formation of expansion cracks, ensure the integrity of the kerogen plug sample, significantly improve the compression success rate, and reduce manpower, material and time costs. This technology provides a competitive technical means for the field of artificial shale preparation, provides strong support for the development of related research, and has important innovation and application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a flow chart of a method for preparing an uncemented artificial kerogen plug sample according to Example 1 of the present invention;
[0031] Figure 2 This is a flow chart of separation of solid organic matter in shale according to Example 1 of the present invention;
[0032] Figure 3 This is a multi-stage compression flow chart of the uncemented artificial kerogen plug sample of Example 1 of the present invention;
[0033] Figure 4 This is a schematic structural diagram of a dry non-cemented artificial kerogen plug prepared in Example 1 of the present invention;
[0034] Figure 5 The microscopic and microstructural characteristics of the uncemented artificial kerogen plug sample of Example 1 of the present invention;
[0035] Figure 6 This is a relationship diagram between elastic wave velocity and porosity of solid organic matter plug samples with different maturity levels according to the present invention. DETAILED DESCRIPTION
[0036] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. Any features such as preparation means, materials, structures or composition ratios not clearly described in this technical solution are regarded as common technical features disclosed in the prior art.
[0037] The following examples select three shale samples with different maturity, including the immature Youganwo Formation shale, the low-mature Chang 7 shale and the over-mature Longmaxi Formation shale.
[0038] Example 1
[0039] like Figure 1 As shown, this embodiment provides a method for preparing a kerogen plug sample of immature Youganwo Formation shale, and the technical solution adopted is:
[0040] Firstly, the immature Youganwo Formation shale samples were crushed into powder, and then the powder samples were subjected to pretreatment, acid treatment, pyrite treatment, heavy liquid flotation and freeze drying, and chloroform washing of soluble organic matter to obtain kerogen powder; distilled water was added to the kerogen powder and fully stirred, and the evenly stirred mixture of kerogen powder and distilled water was slowly added into a pressing mold in batches, and then the pressing mold was placed under a hydraulic press and pressurized to the final pressure; after the kerogen powder was kept at the final pressure for a period of time, the pressure was unloaded, and then the sample was demoulded, and the pressed kerogen plunger sample was dried to obtain a non-cemented artificial kerogen plunger sample.
[0041] The specific steps are:
[0042] (1) The immature Youganwo Formation shale samples were crushed into 180 μm (80 mesh) powder samples. 15 g of the sample was weighed and soaked in distilled water for 2 h to remove the upper liquid and impurities.
[0043] (2) Acid treatment:
[0044] ① First acid treatment: add 120mL 6mol / L hydrochloric acid and stir at 60℃ for 2h to fully dissolve the carbonate in the sample, then discard the acid solution, wash with distilled water until it is weakly acidic, and finally remove the clear solution;
[0045] ② Second acid treatment: add 36mL 6mol / L hydrochloric acid and 54mL 40% hydrofluoric acid, stir at 60℃ for 2h to remove silicate minerals in the sample, then discard the acid solution, wash three times with 1mol / L hydrochloric acid, and finally remove the clear solution;
[0046] ③ The third acid treatment: add 120mL of 6mol / L hydrochloric acid, stir at 60℃ for 1h to fully dissolve the carbonate in the sample, then discard the acid solution, wash three times with 1mol / L hydrochloric acid, and finally remove the clear solution;
[0047] ④ The fourth acid treatment: add 36mL 6mol / L hydrochloric acid and 54mL 40% hydrofluoric acid, stir at 60℃ for 2h to remove silicate minerals in the sample, then discard the acid solution, wash three times with 1mol / L hydrochloric acid, and finally remove the clear solution;
[0048] ⑤Fifth acid treatment: add 120mL of 6mol / L hydrochloric acid and stir at 60℃ for 1h to fully dissolve the carbonate in the sample. Then discard the acid solution, wash three times with 1mol / L hydrochloric acid, remove the clear liquid, and wash with distilled water until it is weakly acidic. Finally, remove the clear liquid.
[0049] (3) Pyrite treatment: Add 20 mL of 6 mol / L hydrochloric acid to each gram of kerogen, and add arsenic-free zinc particles at a frequency of 4 g each time. The pyrite treatment is carried out at 25°C. After adding three times, almost no hydrogen sulfide gas is released, and it is washed with distilled water until there is no halide ion.
[0050] (4) Heavy liquid flotation and freeze drying: Add relative density of 2.1 g / cm 3 The ZnBr2-KBr heavy liquid was centrifuged at 2000r / min in a centrifuge for 20 minutes. After stratification, the upper kerogen was taken out and the inorganic minerals at the bottom of the centrifuge tube were removed. The kerogen sample was then placed in a -5°C refrigerator and frozen for 6 hours. After the ice melted, it was taken out and dried in an oven at 60°C for 72 hours to obtain an enriched kerogen sample.
[0051] (5) Washing soluble organic matter with chloroform: Soxhlet extraction method was used with 100 mL of chloroform as the extraction solvent to completely extract the soluble organic matter, and then the solid organic matter was further purified. It was then dried in an oven at 60°C for 72 h to obtain high-purity kerogen powder.
[0052] (6) 23 g of kerogen powder and 2.3 mL of distilled water were mixed in a mass ratio of 10:1 and stirred for 0.5 h to make the mixture of distilled water and kerogen powder have a certain viscosity; the uniformly mixed mixture of distilled water and kerogen powder was slowly added into the pressing mold in three batches. Each batch of powder was compacted with a pressure column to ensure uniform force during the pressing process. The pressing mold was then placed under a hydraulic press and pressurized. The pressure was maintained at the intermediate pressure for 0.5 h, and then the pressure was directly increased to the final pressure of 20 MPa and maintained. 6h, then reduce the pressure every 5MPa, and the pressure holding time for each reduction is 0.5h, 1h, and 1.5h respectively. It takes 6h to reduce the pressure from 5MPa to 0MPa. Finally, unload the mold and demould the sample to take out the pressed kerogen plunger sample. Put it into the oven and dry it at 60℃ for 3 days. Then weigh the sample, continue drying for 30 minutes, and weigh it again until the mass difference after two dryings is less than 0.01g, ensuring that the distilled water in the sample is completely volatilized, and obtain the non-cemented artificial kerogen plunger sample, such as Figure 4 shown.
[0053] Example 2
[0054] like Figure 1 As shown, this embodiment provides a method for preparing a kerogen plug sample of low-maturity Chang 7 shale, and the technical solution adopted is:
[0055] Firstly, the low-maturity Chang 7 shale sample was crushed into powder, and then the powder sample was subjected to pretreatment, acid treatment, pyrite treatment, heavy liquid flotation and freeze-drying, and soluble organic matter was washed with chloroform to obtain kerogen powder; distilled water was added to the kerogen powder and fully stirred, and the evenly stirred mixture of kerogen powder and distilled water was slowly added into the pressing mold in batches, and then the pressing mold was placed under a hydraulic press and pressurized to the final pressure; after the kerogen powder was kept at the final pressure for a period of time, the pressure was unloaded, and then the sample was demoulded, and the pressed kerogen plunger sample was dried to obtain a non-cemented artificial kerogen plunger sample.
[0056] The specific steps are:
[0057] (1) The low-maturity Chang 7 shale sample was crushed into a powder sample of 180 μm (80 mesh). 15 g of the sample was weighed and soaked in distilled water for 2 h to remove the upper liquid and impurities.
[0058] (2) Acid treatment:
[0059] ① First acid treatment: add 120mL 6mol / L hydrochloric acid and stir at 60℃ for 2h to fully dissolve the carbonate in the sample, then discard the acid solution, wash with distilled water until it is weakly acidic, and finally remove the clear solution;
[0060] ② Second acid treatment: add 36mL 6mol / L hydrochloric acid and 54mL 40% hydrofluoric acid, stir at 60℃ for 2h to remove silicate minerals in the sample, then discard the acid solution, wash three times with 1mol / L hydrochloric acid, and finally remove the clear solution;
[0061] ③ The third acid treatment: add 120mL of 6mol / L hydrochloric acid, stir at 60℃ for 1h to fully dissolve the carbonate in the sample, then discard the acid solution, wash three times with 1mol / L hydrochloric acid, and finally remove the clear solution;
[0062] ④ The fourth acid treatment: add 36mL 6mol / L hydrochloric acid and 54mL 40% hydrofluoric acid, stir at 60℃ for 2h to remove silicate minerals in the sample, then discard the acid solution, wash three times with 1mol / L hydrochloric acid, and finally remove the clear solution;
[0063] ⑤Fifth acid treatment: add 120mL of 6mol / L hydrochloric acid and stir at 60℃ for 1h to fully dissolve the carbonate in the sample. Then discard the acid solution, wash three times with 1mol / L hydrochloric acid, remove the clear liquid, and wash with distilled water until it is weakly acidic. Finally, remove the clear liquid.
[0064] (3) Pyrite treatment: Add 20 mL of 6 mol / L hydrochloric acid to each gram of kerogen, and add arsenic-free zinc particles at a frequency of 4 g each time. The pyrite treatment is carried out at 25°C. After adding three times, almost no hydrogen sulfide gas is released, and it is washed with distilled water until there is no halide ion.
[0065] (4) Heavy liquid flotation and freeze drying: Add relative density of 2.1 g / cm 3 The ZnBr2-KBr heavy liquid was centrifuged at 2000r / min in a centrifuge for 20 minutes. After stratification, the upper kerogen was taken out and the inorganic minerals at the bottom of the centrifuge tube were removed. The kerogen sample was then placed in a -5°C refrigerator and frozen for 6 hours. After the ice melted, it was taken out and dried in an oven at 60°C for 72 hours to obtain an enriched kerogen sample.
[0066] (5) Washing soluble organic matter with chloroform: Soxhlet extraction method was used with 100 mL of chloroform as the extraction solvent to completely extract the soluble organic matter, and then the solid organic matter was further purified. It was then dried in an oven at 60°C for 72 h to obtain high-purity kerogen powder.
[0067] (6) 23 g of kerogen powder and 2.3 mL of distilled water were mixed in a mass ratio of 10:1 and stirred for 0.5 h to make the mixture of distilled water and kerogen powder have a certain viscosity; the uniformly mixed mixture of distilled water and kerogen powder was slowly added into the pressing mold in three batches. Each batch of powder was compacted with a pressure column to ensure uniform force during the pressing process. The pressing mold was then placed under a hydraulic press and pressurized. The pressure was maintained at the intermediate pressure for 0.5 h, and then the pressure was directly increased to the final pressure of 20 MPa and maintained. The pressure was maintained for 6 hours, and then the pressure was reduced every 5 MPa. The pressure was maintained for 0.5 hours, 1 hour, and 1.5 hours each time. The pressure was maintained for 6 hours from 5 MPa to 0 MPa. Finally, the mold was unloaded and the sample was removed from the mold. The pressed kerogen plunger sample was placed in an oven and dried at 60°C for 3 days. The sample was then weighed and dried for another 30 minutes and weighed again until the mass difference after two dryings was less than 0.01 g. This ensured that the distilled water in the sample was completely evaporated to obtain a non-cemented artificial kerogen plunger sample.
[0068] Example 3
[0069] like Figure 1 As shown, this embodiment provides a method for preparing a kerogen plug sample of overmature Longmaxi Formation shale, and the technical solution adopted is:
[0070] Firstly, the overmature Longmaxi Formation shale sample is crushed into powder, and then the powder sample is subjected to pretreatment, acid treatment, pyrite treatment, heavy liquid flotation and freeze drying, and soluble organic matter is washed with chloroform to obtain kerogen powder; distilled water is added to the kerogen powder and fully stirred, and the evenly stirred mixture of kerogen powder and distilled water is slowly added into a pressing mold in batches, and then the pressing mold is placed under a hydraulic press and pressurized to the final pressure; after the kerogen powder is kept at the final pressure for a period of time, the pressure is unloaded, and then the sample is demoulded, and the pressed kerogen plunger sample is dried to obtain a non-cemented artificial kerogen plunger sample.
[0071] The specific steps are:
[0072] (1) The overmature Longmaxi Formation shale sample was crushed into a powder sample of 180 μm (80 mesh). 15 g of the sample was weighed and soaked in distilled water for 2 h to remove the upper liquid and impurities.
[0073] (2) Acid treatment:
[0074] ① First acid treatment: add 120mL 6mol / L hydrochloric acid and stir at 60℃ for 2h to fully dissolve the carbonate in the sample, then discard the acid solution, wash with distilled water until it is weakly acidic, and finally remove the clear solution;
[0075] ② Second acid treatment: add 36mL 6mol / L hydrochloric acid and 54mL 40% hydrofluoric acid, stir at 60℃ for 2h to remove silicate minerals in the sample, then discard the acid solution, wash three times with 1mol / L hydrochloric acid, and finally remove the clear solution;
[0076] ③ The third acid treatment: add 120mL of 6mol / L hydrochloric acid, stir at 60℃ for 1h to fully dissolve the carbonate in the sample, then discard the acid solution, wash three times with 1mol / L hydrochloric acid, and finally remove the clear solution;
[0077] ④ The fourth acid treatment: add 36mL 6mol / L hydrochloric acid and 54mL 40% hydrofluoric acid, stir at 60℃ for 2h to remove silicate minerals in the sample, then discard the acid solution, wash three times with 1mol / L hydrochloric acid, and finally remove the clear solution;
[0078] ⑤Fifth acid treatment: add 120mL of 6mol / L hydrochloric acid and stir at 60℃ for 1h to fully dissolve the carbonate in the sample. Then discard the acid solution, wash three times with 1mol / L hydrochloric acid, remove the clear liquid, and wash with distilled water until it is weakly acidic. Finally, remove the clear liquid.
[0079] (3) Pyrite treatment: Add 20 mL of 6 mol / L hydrochloric acid to each gram of kerogen, and add arsenic-free zinc particles at a frequency of 4 g each time. The pyrite treatment is carried out at 25°C. After adding three times, almost no hydrogen sulfide gas is released, and it is washed with distilled water until there is no halide ion.
[0080] (4) Heavy liquid flotation and freeze drying: Add relative density of 2.1 g / cm 3 The ZnBr2-KBr heavy liquid was centrifuged at 2000r / min in a centrifuge for 20 minutes. After stratification, the upper kerogen was taken out and the inorganic minerals at the bottom of the centrifuge tube were removed. The kerogen sample was then placed in a -5°C refrigerator and frozen for 6 hours. After the ice melted, it was taken out and dried in an oven at 60°C for 72 hours to obtain an enriched kerogen sample.
[0081] (5) Washing soluble organic matter with chloroform: Soxhlet extraction method was used with 100 mL of chloroform as the extraction solvent to completely extract the soluble organic matter, and then the solid organic matter was further purified. It was then dried in an oven at 60°C for 72 h to obtain high-purity kerogen powder.
[0082] (6) 23 g of kerogen powder and 2.3 mL of distilled water were mixed in a mass ratio of 10:1 and stirred for 0.5 h to make the mixture of distilled water and kerogen powder have a certain viscosity; the uniformly mixed mixture of distilled water and kerogen powder was slowly added into the pressing mold in three batches. Each batch of powder was compacted with a pressure column to ensure uniform force during the pressing process. The pressing mold was then placed under a hydraulic press and pressurized. The pressure was maintained at the intermediate pressure for 0.5 h, and then the pressure was directly increased to the final pressure of 20 MPa and maintained. The pressure was maintained for 6 hours, and then the pressure was reduced every 5 MPa. The pressure was maintained for 0.5 hours, 1 hour, and 1.5 hours each time. The pressure was maintained for 6 hours from 5 MPa to 0 MPa. Finally, the mold was unloaded and the sample was removed from the mold. The pressed kerogen plunger sample was placed in an oven and dried at 60°C for 3 days. The sample was then weighed and dried for another 30 minutes and weighed again until the mass difference after two dryings was less than 0.01 g. This ensured that the distilled water in the sample was completely evaporated to obtain a non-cemented artificial kerogen plunger sample.
[0083] Test Example 1
[0084] After drying, the kerogen plug samples prepared in Examples 1-3 were tested for basic physical properties, including density, porosity, and microstructure characterization. The density of the kerogen plug samples was calculated using the gravimetric method by weighing and measuring the volume using a JA1003N-5003N electronic precision balance; the porosity was measured using a KDKDY-Z core porosity meter, and the measurement results are shown in Table 1; the microstructure was observed using a Zeiss Gemini 450 field emission scanning electron microscope. The microstructure characteristics of the kerogen plug samples prepared in Example 1 are shown in Table 1. Figure 5 shown.
[0085] Subsequently, the artificial kerogen plug samples of Examples 1-3 were placed in an ultrasonic pulse velocity test device to conduct an elastic wave velocity measurement experiment. The experiment started with a confining pressure of 5.00 MPa, and gradually increased to a maximum of 30.00 MPa in steps of 5.00 MPa. Ultrasonic velocity measurements were performed under each confining pressure condition. Finally, the elastic wave velocity and porosity at the highest pressure were selected for intersection analysis to explore the relationship between kerogens of different maturity and porosity and maturity, such as Figure 6The analysis shows that the immature Youganwo Formation sample has the lowest porosity, but its elastic wave velocity is only slightly higher than that of the low-maturity Chang 7 sample, even though the latter has twice the porosity of the former. This suggests that porosity has a significant effect on the elastic wave velocity of organic samples, but factors such as thermal maturity also play an important role. In particular, the overmature Longmaxi Formation kerogen, despite having a porosity similar to that of the low-maturity Chang 7 sample, exhibits the highest elastic wave velocity, highlighting the effect of thermal maturity on the elastic properties of organic core samples. The elastic wave velocity of solid organic matter is a comprehensive result of thermal maturity and pore structure evolution.
[0086] Figure 1 Physical property testing
[0087] Example <![CDATA[Density (g / cm 3 )]]> Porosity(%) Example 1 1.15 13.38 Example 2 1.26 30.98 Example 3 1.59 31.35
[0088] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing an uncemented artificial kerogen plug, characterized in that: The steps include: S1. Preparation of kerogen powder: First, crush the fresh rock sample into powder, then perform pretreatment, acid treatment, pyrite treatment, heavy liquid flotation and freeze drying on the powder sample in sequence, wash the soluble organic matter with chloroform, and dry to obtain kerogen powder; S2, batching and stirring: adding distilled water to the kerogen powder prepared in S1 and stirring thoroughly; S3, mold filling and pressing: the mixture of kerogen powder and distilled water stirred evenly in S2 is slowly added into the pressing mold in batches, and then the pressing mold is placed under a hydraulic press and pressurized to the final pressure; S4. Depressurization and demoulding: After maintaining the final pressure for a period of time, the kerogen powder is pressure-unloaded, and then the sample is demoulded. The pressed kerogen plunger sample is dried to obtain a non-cemented artificial kerogen plunger sample.
2. The method for preparing an uncemented artificial kerogen plug according to claim 1, characterized in that: In S1, the particle size of the powder sample is 75 to 180 μm, and the pretreatment includes soaking the powder sample in distilled water for 2 to 4 hours to remove upper liquid and impurities.
3. The method for preparing an uncemented artificial kerogen plug according to claim 1, characterized in that: In S1, the specific process of the acid treatment is: removing carbonate from the sample includes adding hydrochloric acid to the pre-treated sample, heating to 60-70° C., stirring for 1-2 hours, removing the hydrochloric acid, washing with water and removing the washing liquid, wherein the volume of the hydrochloric acid required per gram of the pre-treated sample is 6-8 mL, and the concentration of the hydrochloric acid is 6 mol / L; Removing silicates from the sample comprises adding a mixed acid solution of hydrochloric acid and hydrofluoric acid to the sample after removing carbonates, heating to 60-70° C., stirring for 2 hours, removing the mixed acid solution, washing with water and removing the washing liquid, wherein the mixed acid solution is composed of hydrochloric acid and hydrofluoric acid in a volume ratio of 1-1:2, the concentration of the hydrochloric acid is 6 mol / L, the mass fraction of the hydrofluoric acid is 40%, and the volume of the mixed acid solution required for each gram of the sample after removing carbonates is 6 mL; The steps of removing carbonate from the sample and removing silicate from the sample are repeated alternately until the sample no longer dissolves and its weight decreases.
4. The method for preparing an uncemented artificial kerogen plug according to claim 1, characterized in that: In S1, the specific process of the pyrite treatment is: for the sample after acid treatment, 6 mol / L hydrochloric acid and arsenic-free zinc particles are repeatedly added until the sample does not contain halide ions; The specific process of heavy liquid flotation and freeze drying is: using a relative density of 2.0-2.1 g / cm 3 The samples were subjected to layered flotation with ZnBr2-KBr heavy liquid to extract organic matter from the samples and remove residual inorganic minerals. The samples were then freeze-dried at a freezing temperature of -5°C and a drying temperature of 60°C.
5. The method for preparing an uncemented artificial kerogen plug according to claim 1, characterized in that: In S1, the specific process of washing the soluble organic matter with chloroform is: using the Soxhlet extraction method, using chloroform as the extraction solvent, completely extracting the soluble organic matter, and further purifying the solid organic matter.
6. The method for preparing an uncemented artificial kerogen plug according to claim 1, characterized in that: In S2, the mass ratio of the kerogen powder to distilled water is 10:1, and the stirring time is 0.25 to 0.5 h.
7. The method for preparing an uncemented artificial kerogen plug according to claim 1, characterized in that: In S3, the specific process of pressurization is: first, maintain the pressure at an intermediate pressure for 0.5 h, then directly increase the pressure to the final pressure and maintain the pressure for 6 h, and the final pressure is 20-30 MPa.
8. The method for preparing an uncemented artificial kerogen plug according to claim 1, characterized in that: In S4, the specific process of the pressure unloading is: the pressure is reduced every 5 MPa, and the pressure holding time for each pressure reduction is 0.5 to 6 hours, and the lower the pressure is, the longer the pressure holding time is. When the pressure is reduced from the final pressure to 0 MPa, the pressure holding time is 6 to 8 hours; The drying temperature is 50-60° C., and the drying time is 3-4 days.
9. An uncemented artificial kerogen plug, characterized in that: It is prepared based on the method for preparing an uncemented artificial kerogen plug sample as described in any one of claims 1 to 8.
10. A use of an uncemented artificial kerogen plug according to claim 9, characterized in that: The uncemented artificial kerogen plug sample is used for physical testing of rocks, including density, porosity, microstructure characterization and elastic wave velocity measurement experiments.
Citation Information
Patent Citations
Production method of hot-pressing-based kerogen-containing shale physical model and shale model
CN105601169A
Method for preparing high purity kerogen
CN106596605A
Separating and quantifying method of different occurrence states of soluble organic matter in mud shale
CN108982286A
Kerogen extraction system
CN110314403A
Kerogen elastic modulus test method
CN110836836A